Wśród rekwizytów. Sienkiewiczowski realizm szczegółów - Bujnicki, Tadeusz (Acta Universitatis Lodziensis. Folia Linguistica, 2016)
This article will explore the manner in which Henryk Sienkiewicz used detail and recurrent motifs in his descriptions of landscapes and narrative events in chosen novellas (Hania, Jamioł, Wspomnienie z Maripozy and Z pamiętnika poznańskiego nauczyciela) and two parts of the Trilogy (Ogniem i mieczem and Potop). The following will be considered in more detail: the motif of books (in Wspomnienie z Maripozy, and Z pamiętnika…), and detailed descriptions of manor houses (in the historical novels). The final aim will be to define the basic structures of Sienkiewicz’s realism of detail, and demonstrate that they form an important element of the works’ fictional universe.